Design a Vest using Embedded System for Human Body Vibrations Measurements - Othman A. Smadi, Hitham. M. Tlilan, Rami Al-Jarrah, A. E. Al-Kahloot, A. Kailani (International Journal of Control and Automation, 2020)
This paper shows a design of a vest using an embedded system to measure the response of human body to the mechanical vibrations. The deigned vest contain 56 Piezo-electronic vibration sensors that are distributed at the critical points of the human body. The designed vest considers different types of mechanical machines to make them more safe and applicable for human. This will help in the assessment of the vibrations risk in various applications at critical points of the human body. The obtained frequencies for all scenarios and experiments are within the standard ranges that are suitable to human. The results show that the higher frequencies outputs concentrated along the spine as well as on the chest. Thus, effects of vertical vibrations on the human body cannot be ignored for any application. The next proposed research is to improve the accuracy of the obtained result by improving the sensors attachment to human body.